2021
DOI: 10.3390/biom11030347
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of α2-Plasmin Inhibitor into Fibrin Clots and Its Association with the Clinical Outcome of Acute Ischemic Stroke Patients

Abstract: Cross-linking of α2-plasmin inhibitor (α2-PI) to fibrin by activated factor XIII (FXIIIa) is essential for the inhibition of fibrinolysis. Little is known about the factors modifying α2-PI incorporation into the fibrin clot and whether the extent of incorporation has clinical consequences. Herein we calculated the extent of α2-PI incorporation by measuring α2-PI antigen levels from plasma and serum obtained after clotting the plasma by thrombin and Ca2+. The modifying effect of FXIII was studied by spiking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…Nevertheless, these results suggest that α2-PI could play a role in the pathophysiology of thrombolysis failure and may be an important factor contributing to the inefficacy of therapy in case of severe strokes. Consistent with this finding, we have shown in previous work that the extent of α2-PI incorporation into fibrin clots was the lowest in AIS patients with favorable outcomes after thrombolysis (10). These results are in line with another recent work from our group where we showed that together with age and NIHSS, thrombus burden is the most important indicator of thrombolysis outcome, and the levels of a number of key hemostasis parameters measured on admission or 24 h later showed no association with treatment outcomes in a multivariate model (46).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, these results suggest that α2-PI could play a role in the pathophysiology of thrombolysis failure and may be an important factor contributing to the inefficacy of therapy in case of severe strokes. Consistent with this finding, we have shown in previous work that the extent of α2-PI incorporation into fibrin clots was the lowest in AIS patients with favorable outcomes after thrombolysis (10). These results are in line with another recent work from our group where we showed that together with age and NIHSS, thrombus burden is the most important indicator of thrombolysis outcome, and the levels of a number of key hemostasis parameters measured on admission or 24 h later showed no association with treatment outcomes in a multivariate model (46).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, on admission, only moderately strong correlation was found between the activity and antigen assay results, which then improved post-lysis. This might arise from the fact that the incorporation of α2-PI into the thrombus by FXIIIa primarily involves PB-α2-PI (10,43). It has been suggested by previous reports that the commercially available chromogenic α2-PI activity assay used in this study is mainly sensitive to the levels of PB-α2-PI, the more active and kinetically faster plasmin inhibitor (44,45).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Two recent studies have shown a survival increase for FXIII substitution in trauma patients, suggesting the potential effectiveness of FXIII for the treatment of hemorrhage (37,38). Moreover, increased FXIII levels may result in elevated incorporation of α2plasmin inhibitor (α2-PI), showing an association with the outcome of IVT therapy (39). Therapeutic plasma exchange or albumin solutions enriched FXIII, and purified plasma-derived FXIII may restore coagulation potential, which may be a promising treatment strategy and merits further verification (40,41,42).…”
Section: Discussionmentioning
confidence: 99%